Castellated Beam with and without Stiffners Using ANSYS - Subramani, T; Sukumar, V (International Journal of Engineering and Technology, 2018)
Castellated beam is escalation in vertical bending stiffness, simple carrier provision and appealing look. But one effect of presence of Web beginning will be the development of varied local results. Castellated beams are metal beams with web openings and that they benefit its benefit because of its multiplied depth of phase without any extra weight. To analyze the conduct of castellated metal beams having an I-shaped go-element. Analysis is carried from beam with two factor load and genuinely supported assist condition.Â Â